A comparative and contrastive analysis of linguistic features (morphology, phonology and semantics) on English Advertising (Marketing And Promotion) terminology with their Vietnamese equivalents = Một sự phân tích, so sánh và đối chiếu các đặc trưng ngôn ngữ học ( hình thái học, âm vị học, ngữ nghĩa học) giữa các thuật ngữ quảng cáo tiếng anh và các yếu tố tiếng việt tương đương - Bùi, Thị Phương (2021)
The language of advertising is very special and different from other languages. In this diploma thesis, I will be concerned with the language of advertising. I will scope my attention to the linguistic means used in advertisements. The main reason to choose this topic was my interest in English language and advertising, for the most part from linguistic point of view. I find advertising language fascinating; therefore, I would like to discover its principles, strategies and anatomy of creative writing and grammatical structures. This paper provides the analysis of language of advertising from linguistic point of view and brings knowledge about the use of linguistic devices in advertising. The practical research analyses the advertisements and determines the most widely used linguistic means, even in relation to product specialization. The findings of the study and analysis are useful for familiarizing and understanding the main issues connected with techniques of writing advertising texts; the concrete statements and data can provide information for those who write advertising texts in English. The diploma thesis is addressed to the students of English language for Specific Purposes, teachers of English language for Specific Purposes, people working in advertising sphere, copywriters and all people interested in language of advertising.